Administration Tort Liability For Violating The Human Right To A Healthy Environment - Al-Qaisi, Professor Dr. Hanan Muhammad; Al-Ghalbi, Muhammad Nima (The college of law and political science journal, 2023)
The human right in a healthy environment is one of the new human rights that fall under the third generation of human rights. It is not only a right but also a social value that the legal system must struggle to preserve, whether this legal system is international or internal. This right is not only related to the right of the present generation to live in a healthy environment, but it is also linked to the right of future generations to live in a similar healthy environment. Therefore, nature must be preserved for the benefit of future generations, and this what gives this right a future aspect. Thus, states and international organizations must work to reconcile the necessities of modern technological developments and the limitations they inflict, and the imperatives of ensuring the function of the principle of human enjoyment of a suitable healthy environment, by preserving the environment and protecting it from pollution.The results of violating this right have become clear and evident, as the cause of the damage is obligated to compensate, and this applies to all persons, whether natural or legal, private or public, including the state, as administration is the major polluter, because of its means of production that pushes into the environment many pollutants and toxins, it contributes to the pollution of the environment significantly despite its obligation to protect it, and then the administration is questioned about its violation of the individual’s right to a healthy environment. The study seeks to search for the basis of the administration’s commitment to compensation, especially with the difficulty of attributing the error to it, and exploring the types of compensation, and to which extent we can benefit from the principle of polluter pays